OA33 The top 10 research priorities in psoriatic arthritis: a James Lind Alliance Priority Setting Partnership. (23rd April 2022) - Hailey, Louise; Kinsella, Suzannah; Bundy, Chris; Burstow, Helen; Chandler, David; Cowper, Russ; Helliwell, Philip; Joannes, Lucille; Kelly, Andy; Kennedy, Bronagh; McAteer, Helen; Mukherjee, Sandeep; et al.
Abstract: Background/Aims: This process aimed to identify and prioritise the top 10 research questions or evidence uncertainties for psoriatic arthritis (PsA) in adults. The British Psoriatic Arthritis Consortium (BritPACT) formed a Priority Setting Partnership (PSP) comprising people with PsA, carers and healthcare professionals, in association with the James Lind Alliance (JLA) to identify the key questions and priorities. Methods: The JLA methodology involved a three-stage process: 1. A steering group composed of stakeholders conducted an initial online survey of people with PsA, families, carers and healthcare professionals to identify PsA questions. Participants were asked, "What do you think are the most important unanswered questions in psoriatic arthritis research?". Duplicate questions and those which were out of scope were removed. Questions were checked against existing evidence to establish "true uncertainties", which were then grouped as "indicative questions" reflecting the overarching themes of the original submissions (diagnosis, effects of disease and treatment, flares, psychological, financial and social factors, gender-associated issues, Covid-19 and treatment) to facilitate prioritisation in stage two. 2. In a second online survey, people with PsA, carers and healthcare professionals ranked the "true uncertainties" by importance. 3. During the final workshop, including people with PsA and clinicians, participants worked together to rank the questions to generate a top 10 list of research priorities. Results: The initial survey recruited 317 respondents, submitting a total of 988 questions. The individual submissions generated 46 indicative questions. 69% of the respondents were people with PsA, and 15% were friends, relatives, or carers of someone affected by PsA. In the second survey, 422 respondents, of whom 82% were people with PsA, their carers, relatives or friends, prioritised these uncertainties; 18 of these questions were shortlisted and taken forward to the final online workshop. In the last stage, people with PsA, carers, and healthcare professionals met and reached a consensus on the final top 10 research priorities (Table 1). Conclusion: The top 10 priorities identified will guide PsA research, ensuring that PsA researchers and those who fund research know the most urgent needs of people living with PsA, their families and carers, and those treating people with PsA. Disclosure: L. Hailey: None. S. Kinsella: None. C. Bundy: None. H. Burstow: None. D. Chandler: None. R. Cowper: None. P. Helliwell: None. L. Joannes: None. A. Kelly: None. B. Kennedy: None. H. McAteer: None. S. Mukherjee: None. J. Packham: None. E. Wise: None. H. Young: None. L. Coates: None.